Variation margins, fire sales, and information-constrained optimality - Bruno Biais; Florian Heider; Marie Hoerova (European Central Bank (ECB), 2018)
Protection buyers use derivatives to share risk with protection sellers, whose assets are only imperfectly pledgeable because of moral hazard. To mitigate moral hazard, privately optimal derivative contracts involve variation margins. When margins are called, protection sellers must liquidate some of their own assets. We analyse, in a general-equilibrium framework, whether this leads to inefficient fire sales. If investors buying in a fire sale interim can also trade ex ante with protection buyers, equilibrium is information-constrained efficient even though not all marginal rates of substitution are equalized. Otherwise, privately optimal margin calls are ineffciently high. To address this inefficiency, public policy should facilitate ex-ante contracting among all relevant counterparties.
Keywords: G18; D62; G13; D82; 330; variation margins; fire sales; pecuniary externalities; constrained efficiency; macro-prudential regulation